OʻQUVChILAR TARBIYASIDA MILLIY VA UMUMINSONIY QADRIYATLARNING OʻRNI - Jovliyev, J.A. (SCIENCE and SOCIETY, 2025)
It is shown that the role of national and universal values in the education of young people is invaluable. The importance of educating young people through national values in the educational process was noted.
Keywords: youth; national and universal values; morality; education; upbringing